2017
DOI: 10.1108/jsbed-07-2016-0116
|View full text |Cite
|
Sign up to set email alerts
|

Export promotion programmes and SMEs’ performance

Abstract: Purpose-The purpose of this study is to investigate the network promotion role of export promotion programmes in driving SMEs' export performance. Design/methodology/approach-Drawing on a dual institutional and network based approaches to internationalisation, the study tests an integrative model that explores the mediating role of SMEs' relationships quality in the link between Government Export Promotion Programmes (both informational and experiential forms) and export performance. The model was tested using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(110 citation statements)
references
References 86 publications
(179 reference statements)
6
100
1
3
Order By: Relevance
“…Third, testing the data in a North African country has revealed that the key drivers of export performance in developing countries differs from those generally reported in developed nations. The nonsignificant contribution of technological resources and the proven importance of local relationships are contrary to prior findings gathered from U.K. exporters (Beleska‐Spasova et al, ; Haddoud et al, ). The low‐tech nature of the products exported from Algeria and the collectivist environment where firms operate did influence the determinants of export performance and regularity.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Third, testing the data in a North African country has revealed that the key drivers of export performance in developing countries differs from those generally reported in developed nations. The nonsignificant contribution of technological resources and the proven importance of local relationships are contrary to prior findings gathered from U.K. exporters (Beleska‐Spasova et al, ; Haddoud et al, ). The low‐tech nature of the products exported from Algeria and the collectivist environment where firms operate did influence the determinants of export performance and regularity.…”
Section: Discussioncontrasting
confidence: 99%
“…Relational resources gained through the firms’ connections and collaboration with their foreign partners (importers) are important determinants of export performance (Fafchamps et al, ; Haddoud, Jones, & Newbery, ; Kim & Hemmert, ; Lages, Lages, & Lages, ; Leonidou, Samiee, Aykol, & Talias, ; Ling‐Yee, ; Ural, ). Evidence from the United Kingdom showed that compared to local networks, foreign relationships have a greater influence on SMEs’ export performance (Haddoud et al, ). Foreign networks are particularly useful in creating foreign‐market knowledge and increasing export intensity (Ling‐Yee, ).…”
Section: Conceptual Framework: a Dual Perspectivementioning
confidence: 99%
“…For instance Boso et al (2016) pre-sented that collaboration with international organizations improves quality of the products and services and boost organizational learning culture. Another study conducted by Haddoud et al (2017) claims that technology helps organizations bring innovative products in market. In addition to that, it is also confirmed that external technology improves the employee performance (Haddoud et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Another study conducted by Haddoud et al (2017) claims that technology helps organizations bring innovative products in market. In addition to that, it is also confirmed that external technology improves the employee performance (Haddoud et al, 2017). Moreover, innovativeness was seen in entrepreneurial orientation.…”
Section: Introductionmentioning
confidence: 99%
“…In the light of this clarification, when the mobile phone is modulated with knowledge diffusion variables, relevant networks are created that could enhance entrepreneurship, partly because networks have been recently established to be relevant in the performance of Small and Medium Size enterprises (Haddoud et al, 2017). Entrepreneurship can ultimately be boosted if the underlying modulation of the mobile phone mitigates a number of constraints to the starting and doing of business, notably, the: cost of business start-up procedures; number procedures to enforce a contract; number start-up procedures to register a business; days required to build a warehouse; days required to enforce a contract; days required to register a property; years needed to resolve an insolvency; hours required to prepare and tax taxes; days required to exports and days required to start a business.…”
Section: Mobile Phone Modulation With Knowledge Diffusion Channels Anmentioning
confidence: 99%